Manajemen Sumber Daya Manusia dalam Pondok Pesantren - Mukhibat _ (IAIN Pekalongan, 2012)
As an institution that accompanies the propagation of Islam in Indonesia, Islamic boarding school has four folds of perceptions. It can be viewed as the institution of ritual, moral development, proselytizing and popularly functioned as Islamic education. In line with the shift of educational management paradigm, recently some Islamic boarding schools are also experiencing growth in the aspects of management, organization, and administration. Islamic boarding schools can no longer be managed with the traditional model or approach so as to be able to compete with other kinds of institution. In accord to this, they should always reform them selves to improve the quality of managementand its educational system. In regard to the rapid change of Islamic boarding schools, the strategic efforts of human resources development should be paid greater attention. Human resource development can be done through personal training programs (in instance, organization). These development programs include upgrading work, dedication, moral, discipline, peer skill enhancement and training. In addition, the development can also be done by: (1) institutional development, (2) enhancing the internal-external networking with other institutions, and (3) reorientation of meaning towards Islam by Islamic bardingÂ school.